Analysis of the Speed of Ap Chagi Kick Technique in Taekwondo Senior Athlete Dojang Garuda Satria Banjarbaru City - Ismi Cahya Marshanda; Norma Anggara; Akhmad Amirudin (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study aims to analyze the speed of Ap Chagi's kick technique in senior Taekwondo athletes Dojang Garuda Satria Banjarbaru City. Quantitative descriptive research using an experimental survey design was employed in this investigation. The sample consisted of 15 senior athletes selected using the purposive sampling technique. The measurement was carried out by counting the number of Ap Chagi kicks that were successfully made within 15 seconds using the stopwatch and the target kick. The results showed that of the 15 athletes tested, 5 people (33%) were in the "very good" category, 7 people (47%) were in the "good" category, and 3 people (20%) were in the "adequate" category. No athletes are in the "less" or "less" category The conclusion of this study is that Ap Chagi's kick speed in senior athletes of Dojang Garuda Satria Banjarbaru City is generally in the good to very good category, which reflects good mastery of technique and physical readiness in supporting performance during matches.